Metode Taguchi - PCR TOPSIS untuk Optimasi Energi dan Kecepatan Grafir Mesin Laser - Adi Nugroho; Adhi Setya Hutama (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2019)
Along with technological developments and easy access to insight into creative entrepreneurship, many people are competing to create creative products, one of which is by utilizing laser technology. Laser cutting and engraving is used for the manufacture of engraving products in acrylic, wood, glass, leather etc. The uniqueness of the results of laser engraving is uniform surface roughness and detailed product contours. The main challenge of the laser engraving process is the process of setting parameters that take a long time to get the desired surface roughness. The old process certainly results in high energy consumption which affects the cost of the process. In this study the Taguchi method combined with PCR-TOPSIS was used to optimize the engraving process parameters. The parameters measured are scan speed, nozzle distance to the sample surface, and the percentage of energy for the engraving process. The response parameters consist of the level of surface roughness, processing time, and energy consumption used. The results of the optimization test obtained the engraving speed is 200 mm/s, the percentage of energy released by the laser engrave machine was 10 % and the nozzle distance was 10 mm.